Beyond Blackface : African Americans and the Creation of American Popular Culture, 1890-1930 - Brundage, W. Fitzhugh (William Fitzhugh), 1959- (Book collections on Project MUSE., 2011)
Bringing together original work by 16 scholars in various disciplines, this volume addresses the complex roles of black performers, entrepreneurs & consumers in American mass culture during the early twentieth century.